Kinesio taping application in a pediatric patient with spinal muscular atrophy - Bayram Kelle; Didem Arslan Tas; Erkan Kozanoglu (Çukurova Üniversitesi Tıp Fakültesi Dergisi, 2016)
Kinesio taping is one of the elastic bandage methods which has been quite popular in the last 20 years and has been applied in various musculoskeletal conditions. Although the mechanism of action is not clear, many theories have been suggested so far. In this case report, we aimed to present the results of kinesiotape application for back pain of the patient with spinal muscular atrophy which is one of the progressive muscular disorders. It was performed for three times with four days interval. Fascial technique B (Space technique) was applied. Reduce of pain was also observed during the subsequent applications. The application of kinesio taping could be beneficial on reducing the pain in patients with progressive muscle diseases. [Cukurova Med J 2016; 41(2.000): 386-389]